Academic and professional expectations of immigrant students in secondary education in the Community of Madrid - Gil Gómez, Raquel (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The main objectives of this paper are: to know the prospects of continuing their studies that immigrant pupils in their 4.th year of Secondary Compulsory Education (E.S.O.) and 2.nd year of High School (Bachillerato) at Secondary Education Schools of the Community of Madrid have; to verify if the expectations expressed by these foreign students during the academic year 2004-2005 have been fulfilled, according to the number of them who actually attend school in the academic year 2005-2006; and to offer specific public organizations within the Administration of the Community of Madrid relevant information about the social and educational integration of the group of young immigrant population in the framework of the educational offer at the end of Secondary Compulsory Education and High School (Bachillerato). As the most important conclusion, the main hypothesis of this project can be confirmed: there is a meaningful correlation between foreign students in their 4.th year of Secondary Compulsory Education (E.S.O.) and 2.nd year of High School in the academic year 2004-2005 expecting to continue their studies and those who actually continue studying during the following year 2005-2006
Keywords: Academic expectations; Professional expectations; Immigrant pupils; Education